BIOPHILIC DESIGN-BASED COMMUNITY MENTAL HEALTH SERVICE CENTER IN MEDAN CITY - Hasyen, Muhammad Nuzil Qirani Al; Aulia , Dwira Nirfalini (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Focusing on actively involving the potential of the community creates a new paradigm in community mental health, encompassing the management of mental health issues through promotive, preventive, curative, and rehabilitative aspects. This concept serves as a foundation for an integrated mental health service center, given that mental health service facilities in Indonesia, particularly in Medan, remain limited and suboptimal. The biophilic design concept offers an approach that enhances the environmental quality of healthcare facilities by integrating natural elements to support the holistic healing process of patients. Thus, biophilic design can serve as an innovative solution for developing more holistic and sustainable mental health facilities, especially in Medan. This study is expected to serve as a reference for the design of other mental health facilities in Indonesia.